Synthesis and evaluation of SPION@CMD@Ser-LTVSPWY peptide as a targeted probe for detection of HER2+ cancer cells in MRI - Arash Papi; Rasoul Irajirad; Milad Yousefvand; Ali Reza Montazerabadi; Zahra Mohammadi (Nanomedicine Journal, 2021)
Objective(s): Successful detection of tumors in the early stages can significantly increase a patient’s healing process and recovery speed. Conventional imaging techniques usually depend on the tissues’ anatomical structure. Epidermal growth factor receptor-2 (HER-2) is a transmembrane protein with an extracellular ligand-binding domain. HER2 plays an essential role in cell proliferation, differentiation, and survival, and its overexpression is associated with various cancers, especially breast and ovarian cancers. Access to its extracellular domain makes HER2 an ideal target for drug preparation and molecular imaging probes. In this study, a targeted magnetic nanoprobe for molecular imaging of HER2 positive cancers was synthesized, and also its potential as a T2-weighted targeted contrast agent was assessed.Materials and Methods: Superparamagnetic SPION nanoparticles were synthesized using the co-precipitation method in the presence of CMD and were labeled with SLTVSPWY peptide. The SPION@CMD@SLTVSPWY nanocomplex was characterized by TEM, DLS, XRD, AAS, FTIR, EDX, and VSM. The r1 and r2 relaxivities were then calculated using a 1.5 Tesla clinical magnetic field. The cytotoxicity of the nanocomplex was evaluated by MTT assay. Finally, the difference between uptake of targeted nanocomplexes and SPION by the human SKOV-3 cell line (HER2 +) was investigated.Results: The SPION@CMD NPs were synthesized with spherical shape and superparamagnetic behavior. Characterization results confirmed the formation of SPION@CMD@SLTVSPWY.  r2 relaxivity and r2/r1 calculations resulted in suitable values of 313 mM-1s-1 and 8.05 for SPION@CMD@SLTVSPWY, respectively. Increased uptake of targeted nanocomplexed (SPION@CMD@SLTVSPWY) compared to non-targeted NPs (SPION@CMD) was very noticeable visually, and its numerical ratio was 3.51 at a concentration of 0.075 mM.  Conclusion: The targeted synthesized nanocomplex in this study has great potential as a T2 weighted probe contrast agent in MR imaging owing to its appropriate high uptake in HER2 + cells.